Respuesta :
Answer:
-64
Step-by-step explanation:
The expression is written as
[tex]\displaystyle \left (\frac{j\ k^{-2}}{j^{-1}\ k^{-3}}\right )^3[/tex]
We need to apply the rules of power of power in algebra:
[tex](x^m)^n=x^{m.n}[/tex]
Also, we apply the quotient of variables
[tex]\displaystyle \left (\frac{x^m}{x^n}\right )=x^{m-n}[/tex]
Let's simplify the given expression
[tex]\displaystyle \left (\frac{j^3\ k^{-6}}{j^{-3}\ k^{-9}}\right)[/tex]
[tex]=j^{3+3}k^{-6+9}[/tex]
[tex]=j^6k^3[/tex]
For j=-2 and k=-1
[tex]=(-2)^6(-1)^3[/tex]
[tex]=64\times(-1)[/tex]
[tex]\boxed{-64}[/tex]